(untitled) (Law, State and Telecommunications Review, 2020)
Purpose ”“ The objective of this article is to establish whether digital connectivity meets the criteria required by Colombian constitutionalism to be considered as a fundamental right, specifically in relation to access and effective use of the internet. Methodology ”“ The methodology used consisted of going to the existing literature in books, specialized magazines and sentences issued by the Constitutional Court, establishing the differences and similarities in the data obtained, and then performing an analysis of the information collected. Originality/value ”“ The originality component of this article means that the study was developed based on innovative criteria for the configuration of new fundamental rights. Findings ”“ Finally, it is concluded that there can be no social justice without digital connectivity.